Urotensin II Induces Mice Skeletal Muscle Atrophy Associated with Enhanced Autophagy and Inhibited Irisin Precursor (Fibronectin Type III Domain Containing 5) Expression in Chronic Renal Failure - Ya-Jing Pan; Si-Jia Zhou; Jin Feng; Qiong Bai; La-Ta A; Ai-Hua Zhang (Karger Publishers, 2019)
Background/Aims: Skeletal muscle atrophy is one of the main manifestations of protein energy wasting. We hypothesized that urotensin II (UII) can lead to skeletal muscle atrophy through upregulating autophagy and affecting Irisin precursor fibronectin type III domain containing 5 (FNDC5) expressions. Methods: Three animal models (the sham operation, wild-type C57BL/6 mice with 5/6 nephrectomy, UII receptor (UT) gene knockout (UTKO) mice with 5/6 nephrectomy) were designed. Skeletal muscle weight, cross-sectional area (CSA) along with UII, FNDC5, LC3, and p62 expression were investigated. C2C12 cells were differentiated for up to 4 days into myotubes. These cells were then exposed to different UII concentrations (10-5 to 10-7 M) for 6-12 h and analyzed for the expressions of autophagic markers. These cells were also exposed to the same predetermined UII concentrations for 48-72 h and analyzed for the FNDC5 expression. Myotube diameter was measured. Results: Upregulation of UII expression in skeletal muscle tissue was accompanied by reduced muscle weight and skeletal muscle CSA in the 2 posterior limbs, upregulated autophagy markers expression, and downregulated FNDC5 expression in 5/6 nephrectomy mice. The decrease of skeletal muscle weight, skeletal muscle CSA, downregulation of FNDC5 expression, and the upregulation of autophagy markers were inhibited in UTKO with 5/6 nephrectomy mice. Our in vitrostudy showed that UII could directly decrease myotube diameter, induce autophagy markers upregulation, and inhibit expression of FNDC5. When UII receptor gene was interfered by UT-specific siRNA, UII induced autophagy markers upregulation and FNDC5 downregulation were inhibited. Conclusion: We are the first to verify UII induces mice skeletal muscle atrophy associated with enhanced skeletal muscle autophagy and inhibited FNDC5 expression in chronic renal failure.